Investigation on the AE characteristics and progressive failure behaviors of tunnels by strength reduction method - Xianhui Feng; Yadav Kedar Prasad; Bin Gong; Xiaofeng Cheng; Wenshuo Duan; Huilin Liu; Fenhua Ren (Frontiers in Earth Science)
The fracture features and failure mechanisms of tunnels excavated in shallow and deep rock masses are investigated using a series of three-dimensional heterogeneous models that incorporate cross section, tunnel alignment, faults and tunnel support system. The strength reduction method is embedded in the rock failure process analysis method to achieve the gradual fracture process, macro failure mode and safety factor, and to reproduce the characteristic fracture phenomenon of surrounding rock masses. The mechanical mechanisms and acoustic emission energy of deep rocks at the different stages of the whole formation process of zonal disintegration are further discussed. The results indicate that the zonal disintegration process is triggered by the stress redistribution; cross section influences the stress buildup, stress shadow and stress transfer as well as the failure mode of surrounding rock mass; the dip of faults and tunnel support system can affect zonal disintegration pattern near the tunnel surface along their strikes; the twin-tunnel layout makes zonal disintegration pattern more intricate. These insights advance our understanding of the zonal disintegration in deep engineering.